Superheating in coated niobium. (7th November 2017) - Junginger, T; Wasserman, W; Laxdal, R E
Abstract: Using muon spin rotation it is shown that the field of first flux penetration H entry in Nb is enhanced by about 30% if coated with an overlayer of Nb3 Sn or MgB2 . This is consistent with an increase from the lower critical magnetic field H c 1 up to the superheating field H sh of the Nb substrate. In the experiments presented here coatings of Nb3 Sn and MgB2 with a thickness between 50 and 2000 nm have been tested. H entry does not depend on material or thickness. This suggests that the energy barrier at the boundary between the two materials prevents flux entry up to H sh of the substrate. A mechanism consistent with these findings is that the proximity effect recovers the stability of the energy barrier for flux penetration, which is suppressed by defects for uncoated samples. Additionally, a low temperature baked Nb sample has been tested. Here a 6% increase of H entry was found, also pushing H entry beyond H c 1 .